Socioeconomic Study of Tourism Activity in Costa Rica: A District-Level Analysis for the Period 1984–2010. - Alvarado Muñoz, Erick (2011)
The general objective of this research was to determinate if the tourist districts had a better result in socioeconomic indicators that the non-tourist districts between the years 1984-2000, and make a qualitative analysis to La Fortuna and Jacó until 2010. Two quasi-experiments and two case analysis were made. The results of quasi-experiments indicate that although the tourist districts of Costa Rica submitted a socioeconomic improvement between 1984 and 2000, this change was not significantly different to that presented in non-tourist districts, in other words, a district in which significantly developed tourism, socioeconomic improvement was not different from any other district in which it developed some other productive activity. Hypotheses were established to explain these results and were exploredthrough case studies.